(untitled) (Law and Safety, 2022)
Corruption is a negative dynamic objectively existing social phenomenon, which necessitates its constant research in order to create new, change existing mechanisms for its detection, prevention and counteraction. In the process of working on a scientific article, such general scientific methods as hermeneutic and classification method were used. The hermeneutic method was used during the analysis of the etymological meaning of the term corruption and certain provisions of international legal acts, the Law of Ukraine “On Prevention of Corruption”. The method of classification was used in the process of dividing the concept of “corruption” into types. Among the special scientific methods logical-semantic and logical-legal were used. They allowed us to formulate the main features of corruption as a legal phenomenon. The main features of corruption: 1) committed by a special subject of law; 2) is performed within the scope of official authority or related opportunities; 4) is committed for the purpose of obtaining illegal benefit for oneself or other persons; 5) is committed in a certain form (the legislator establishes two forms of corruption: a) acceptance of illegal benefit or acceptance of a promise / proposal of illegal benefit; b) a promise / proposal or provision of illegal benefit to a person specified in Part 1 of Art. 3 of the Law of Ukraine “On Prevention of Corruption”); 6) the result is improper performance of duties. The main criteria for the division of corruption into types are the territorial feature, form of commission, duration, sphere of life, type of legal responsibility to which a person is brought for committing corruption. On a territorial basis, a distinction should be made between domestic (national) and transnational corruption, depending on the form of corruption - bribery, fraud, extortion, embezzlement (misappropriation) of public funds, clientelism, lobbying, favoritism, nepotism, state capture. In addition to these types of corruption, based on the definition of this legal phenomenon, which gives the legislator in the Law of Ukraine “On Prevention of Corruption”, depending on the form of corruption, the following types should be distinguished: acceptance of illegal gain; acceptance of a promise / proposal of illegal benefit. According to the time of action, a distinction should be made between one-time (one-time action) and prolonged corruption; depending on the sphere of life there is political, economic, managerial, social, legal corruption; depending on the type of legal liability there is corruption, for which the legislator provides for criminal, administrative, civil, disciplinary liability.